Development of GPS Track and Trace System in Dewantara Smart City Application to Realise Mobile-based Good Governance and Clean Government - Ananda Faridhatul Ulva; Kurniawati Kurniawati; Desvina Yulisda (CV. Media Digital Publikasi Indonesia, 2023)
Smart cities with GPS track and trace implementation have great potential to achieve good and clean governance. This technology enables the government to gather and analyse real-time data concerning mobility, public assets, and the allocation of funds. With precise and transparent information, the government can enhance efficiency, accountability, and responsiveness to the needs of the public. The primary goals of this application are to promote transparency, improve the management of community activities, and encourage community engagement. The approach employed in the creation and development of this smart city application follows the waterfall method. This methodology simplifies the system's initial development and its potential for future enhancements. The results from implementing and testing the smart city system, utilizing usability testing, yield scores exceeding 3, specifically 3.56. This indicates that both government officials and the community find the system and application highly user-friendly